간호대학생의 봉사활동, 자아존중감 및 직업존중감이 전공만족도에 미치는 영향 - 신미아(Mi-A Shin) (한국콘텐츠학회 논문지, 13(11), 2013)
The purpose of this study was to investigate on the effects of volunteering, self-esteem and job-esteem on major satisfaction among the nursing students. This study used a descriptive research design. The participants of this study were 339 nursing students at 2 university in south and north Jeolla-do. 34.8% of the respondents have done volunteer work. Self-esteem was significantly affected by sex, religion, economic status, satisfaction of school life and Job-esteem was significantly affected by religion, satisfaction of school life. Major satisfaction was significantly affected by grade, economic status, satisfaction of school life. Satisfaction on the volunteering work had significant effect on the self-esteem statistically and volunteering experience and the number of volunteering has significant effect on the job-esteem. Major satisfaction was significantly affected by the number of volunteering work, days of volunteering and satisfaction in volunteering work. Related factors affecting major satisfaction was satisfaction of school life, self-esteem and job-esteem. Through this result, it could be suggested that is a need for a strategies to increase satisfaction of school life, self-esteem and job-esteem in order to improve major satisfaction among nursing students. 본 연구는 간호대학생의 봉사활동, 자아존중감 및 직업존중감이 전공만족도에 미치는 영향을 파악하기 위한 서술적 조사연구로, 전라남북도에 소재한 2개 대학교의 간호학과에 재학 중인 1~4학년 339명을 대상으로 하였다. 봉사활동은 대상자의 34.8%가 경험이 있는 것으로 나타났다. 일반적 특성에 따른 자아존중감은 성별, 종교, 경제상태, 학교생활만족에서 유의미한 차이를 보였으며 직업존중감은 종교와 학교생활만족에서 전공만족도는 학년, 경제상태, 학교생활만족에서 유의미한 차이를 보였다. 봉사활동 특성에 따른 자아 존중감은 봉사활동만족에서 유의미한 차이를 보였으며, 직업존중감은 봉사활동경험과 봉사활동횟수에서 그리고 전공만족도는 봉사활동횟수, 봉사활동일, 봉사활동만족에서 유의미한 차이를 보였다. 전공만족도에 영향을 미치는 요인은 학교생활만족, 자아존중감, 직업존중감으로 나타났다. 이러한 결과를 볼 때, 간호대학생의 전공만족도를 향상시키기 위해서는 학교생활만족, 자아존중감 및 직업존중감을 높일 수 있는 전략이 필요함을 확인할 수 있었다.